Архетип Любви в духовной визии Леси Украинки и его музыкальный дискурс - Драганчук-Кашаюк, Виктория Николаевна (Czasopismo Akademii Pomorskiej w Słupsku, 2018)
The discourse of the Ukrainian musical culture is contains numerous appeals to the poetic legacy by Lesya Ukrainka. Therefore, understanding the musical-theatrical, choral, chamber-vocal works by M. Lysenko, K. Stetsenko, Y. Stepovy, S. Lyudkevych, M. Skorulsky, S. Turkevych-Lukiyanovych, V. Kyreiko, I. Shamo, Y. Stankovych, L. Dychko, O. Kozarenko, V. Tymozhinsky and other composers who entered into a musical and poetic dialogue with the poetess, is provides an understanding the key positions of the poet’s philosophy. In our opinion, a new spiritual vision was born in the Lesya Ukrainka’s creative matrix, which embodied the Ukrainian mental Ego in the female image of a spiritual knight and presented it as a weighty component of world culture. More than a hundred years ago, the poet showed a woman’s personality as a com-creator, which has a divine beginning, and therefore we interpret its philosophy in the vein of Femin-personalism (the term is proposed). The three Love types which were shown in Lesya Ukrainka’s works and in her musical discourse are as follows: Ancient Greek „agapeˮ (in variants Love-Spirit, Love-Soul, Love-Eros), Love as a component of national Ego-concept, Love as an immortal divine spirit. The musical discourse expects the interpretation of the drama „Obsessedˮ and others from the „Blue Roseˮ to „Cassandraˮ, „In the Catacombsˮ, „Rufin and Priscillaˮ and others.
The Love archetype in Lesya Ukrainka’s spiritual vision and it’s musical discourse
Keywords: Lesja Ukrainka’s creation; Love archetype; opera; ballet; vocal lyric; musical discourse; Ego-concept; Femin-personalism; творчість Лесі Українки; архетип Любові; опера; балет; вокальна лірика; музичний дискурс; Его-концепт; фемін-персоналізм; творчество Леси Украинки; архетип Любви; вокальная лирика; музыкальный дискурс; Эго-концепт; фемин-персонализм